Longitudinal associations between socioeconomic status and cardiovascular disease in a Chinese population: Evidence from CHARLS - Qingping Zeng; Mengqian Liao; Yu Li; Fei She; Ping Zhang (PLoS ONE, 2025)
Importance The relationship between socioeconomic status and cardiovascular disease among the general Chinese population is inconclusive. Objective This study aims to investigate the relationship between socioeconomic status and cardiovascular disease in the Chinese general population through a large sample. Design We retrospectively analyzed data from the 2015 and 2018 waves of the China Health and Retirement Longitudinal Study (CHARLS). Participants were required to be at least 45 years old and have cardiovascular disease (CVD) data. The study was divided into two parts: a cross-sectional analysis using 2015 data, and a longitudinal analysis of participants without CVD in 2015 but with complete follow-up data in 2018. Socioeconomic status (SES) was assessed using self-reported household income, occupation, education level, and health insurance. CVD events were identified through participant-reported diagnoses of heart disease or stroke. Logistic and Cox proportional hazards regression models were used to estimate the association between SES and CVD. Participants 16,560 participants were included in the cross-sectional analysis and 11,587 in the longitudinal analysis. Exposures Socioeconomic status. Main outcomes and measures Cardiovascular disease, heart disease, and stroke. Results In the cross-sectional analysis, 16% of the 16,560 participants had CVD, with higher prevalence in lower SES groups. After adjustments, middle SES was significantly associated with increased CVD risk (OR 1.77, 95% CI 1.21–2.58). In the longitudinal analysis, during a 3-year follow-up, 12.1% of 11,587 participants developed CVD. Middle SES was associated with a 67% higher risk of new-onset CVD (HR 1.67, 95% CI 1.02–2.74). Sensitivity analysis confirmed these findings, with middle SES showing a significant association with CVD risk (HR 1.32, 95% CI 1.04–1.67). Conclusions and relevance In the general population of China, middle socioeconomic status is positively associated with cardiovascular disease and is more likely to be associated with new-onset cardiovascular disease. Our findings support the need for trade-offs between socioeconomic status groups to benefit different populations, especially considering the middle socioeconomic status group, which is an easily overlooked group. However, more long-term prospective studies are needed to further elucidate the relationship between changes in socioeconomic status and cardiovascular disease in China.